Short-Term Adaptation of Joint Position Sense Occurs during and after Sustained Vibration of Antagonistic Muscle Pairs - Gonzales, Tomas I.; Goble, Daniel J. (Frontiers in Human Neuroscience, 2014)
Proprioception is critical for the control of many goal-directed activities of daily living. While contributions from skin and joint receptors exist, the muscle spindle is thought to play an important role in allowing accurate judgments of limb position and movement to occur. The discharges elicited from muscle spindles can be degraded by simultaneous agonist-antagonist tendon vibration, causing proprioception to be distorted. Despite this, changes in limb perception that may result from sensory adaptation to this stimulus remain misunderstood. The purpose of this study was, therefore, to investigate short-term proprioceptive adaptation resulting from vibration of antagonistic muscle pairs. We measured elbow joint position sense in 21 healthy young adults while 80 Hz vibration was applied simultaneously to the distal tendons of the elbow flexor and extensor muscles. Matching errors were then analyzed during early and late adaptation phases to assess short-term adaptation to the vibration stimuli. Participants committed significant undershoot errors during the early adaptation phase, but were comparable to baseline measurements during the late adaptation phase. When we removed the vibration stimuli and conducted a second joint position matching task, matching variability increased significantly, and participants committed overshoot errors. These results bring into question the efficacy of simultaneous agonist-antagonist tendon vibration to degrade proprioceptive acuity.